Sex-related differential item functioning of the Jenkins Sleep Scale: a cross-sectional study among 77 967 employees in the Finnish public sector - Jussi Vahtera; Mika Kivimäki; Saana Myllyntausta; Jenni Ervasti; Jari P A Arokoski; Mikhail Saltychev; Juhani Juhola (BMJ Open, 2024)
Objectives To investigate if the Jenkins Sleep Scale (JSS) demonstrates sex-related differential item functioning (DIF).Design Cross-sectional study.Setting Survey data from the Finnish Public Sector study (2015–2017).Participants 77 967 employees in the Finnish public sector, with a mean age of 51.9 (SD 13.1) years and 82% women.Outcome measures Item response theory estimates: difficulty and discrimination parameters of the JSS and differences in these parameters between men and women.Results The mean JSS total score was 6.4 (4.8) points. For all four items of the JSS, the difficulty parameter demonstrated a slight shift towards underestimation of the severity of sleep difficulties. The discrimination ability of all four items was moderate to high. For the JSS composite score, overall discrimination ability was moderate (0.98, 95% CI 0.97 to 0.99). Mild uniform DIF (p<0.001) was seen: two items showed better discrimination ability among men and two others among women.Conclusions The JSS showed overall good psychometric properties among this healthy population of employees in the Finnish public sector. The JSS was able to discriminate people with different severities of sleep disturbances. However, when using the JSS, the respondents might slightly underestimate the severity of these disturbances. While the JSS may produce slightly different results when answered by men and women, these sex-related differences are probably negligible when applied to clinical situations.